Anti-inflammatory compounds from the mangrove endophytic fungus Amorosia sp. SCSIO 41026 - Ren, Xue; Chen, Chunmei; Ye, Yuxiu; Xu, Ziying; Zhao, Qingliang; Luo, Xiaowei; Liu, Yonghong; Guo, Peng (Frontiers in Microbiology, 2022)
Three undescribed chlorinated compounds, including two propenylphenol derivates, chlomophenols A and B (1 and 2), and one benzofuran derivate, chlomophenol C (3), together with 16 known compounds, were isolated from the mangrove-endophytic fungus Amorosia sp. SCSIO 41026. 7-Chloro-3,4-dihydro-6,8-dihydroxy-3-methylisocoumarine (4) and 2,4-dichloro-3-hydroxy-5-methoxy-toluene (5) were obtained as new natural products. Their structures were elucidated by extensive spectroscopic analysis and physicochemical properties. Compounds 1, 4, 7, 9, 13, 15, 16, and 19 possessed inhibitory effects against the excessive production of nitric oxide (NO) and pro-inflammatory cytokines in LPS-challenged RAW264.7 macrophages without obvious cytotoxicity. Moreover, the most active one, 5-chloro-6-hydroxymellein (13), further alleviated the pathological lung Injury of LPS-administrated mice and protected RAW264.7 macrophages against LPS-induced inflammation through PI3K/AKT pathway in vivo. Our research laid the foundation for the application of compound 13 as a potential anti-inflammatory candidate.